الخيال الإبداعي في البيئة الجامعية - الفضلي,هدى; يوسف,سليمان (University of Eloued جامعة الوادي, 2024)
ملخص: استقصت الدراسة الحالية الخيال الإبداعي بين المجتمعين المصري والكويتي (ن= 600 من المراهقين الجامعيين العرب) على نحو ما يمكن أن يتبدى من خلال حالتهم الفردية (ذكور – إناث)، وإطارهم الثقافي "الجنسية" (مصرية – كويتية)، وبتطبيق مقياس الخيال الإبداعي لدى المراهقين الجامعيين العرب إعداد/ الباحثان على أفراد عينة الدراسة الأساسية المُقسمة إلى (340) من المصريين، و(260) من الكويتيين، منهم (350 ذكراً) و(250 أنثى)؛ أشارت نتائج الدراسة إلى عدم وجود فروق ذات دلالة إحصائية بين الذكور والإناث من المراهقين الجامعيين العرب في أبعاد الخيال الإبداعي ودرجته الكلية، وكذا عدم وجود فروق ذات دلالة إحصائية بين المراهقين الجامعيين العرب في الثقافتين (المصرية - الكويتية) في أبعاد الخيال الإبداعي ودرجته الكلية. وقد فُسرت النتائج في ضوء أدبيات البحث ومن ثم الخروج بمجموعة من التوصيات في هذا المجال. Abstract: The current study investigated the creative imagination between the Egyptian and Kuwaiti societies (n = 600 Arab university adolescents) as it can be manifested through their individual status (male - female), and their cultural framework "nationality" (Egyptian - Kuwaiti), and by applying the creative imagination scale of Arab University Adolescents Prepared by the two researchers, the main study sample was divided into (340) Egyptians and (260) Kuwaitis, of whom (350 were males) and (250 were females); The results of the study indicated that there were no statistically significant differences between males and females among Arab university adolescents in the dimensions of creative imagination and its total degree, as well as the absence of statistically significant differences between Arab university adolescents in the two cultures (Egyptian - Kuwaiti) in the dimensions of creative imagination and its total degree. The results were interpreted in the light of the research literature, and then came up with a set of recommendations in this field.
دراسة ميدانية على عينتين من المراهقين الجامعيين المصريين والكويتيين من الجنسين
Keywords: الخيال الإبداعي; المراهقين الجامعيين العرب; النوع; الثقافة; Creative imagination; Arab college teens; Gender; The culture